2022
DOI: 10.1111/joa.13714
|View full text |Cite
|
Sign up to set email alerts
|

Comparability of skeletal fibulae surfaces generated by different source scanning (dual‐energy CT scan vs. high resolution laser scanning) and 3D geometric morphometric validation

Abstract: This work aims to test accuracy and comparability of 3D models of human skeletal fibulae generated by clinical CT and laser scanner virtual acquisitions. Mesh topology, segmentation and smoothing protocols were tested to assess variation among meshes generated with different scanning methods and procedures, and to evaluate meshes‐interchangeability in 3D geometric morphometric analysis. A sample of 13 left human fibulae were scanned separately with Revolution Discovery CT dual energy (0.625 mm resolution) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 74 publications
0
12
0
Order By: Relevance
“…The specimens were either digitized through computed tomography (CT) or laser scanning, as previous studies have shown that digital models of long bones from these two acquisition methods are comparable [ 37 , 38 , 39 ]. The acquisition of the 3D models of fibulae belonging to the Raymond A.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The specimens were either digitized through computed tomography (CT) or laser scanning, as previous studies have shown that digital models of long bones from these two acquisition methods are comparable [ 37 , 38 , 39 ]. The acquisition of the 3D models of fibulae belonging to the Raymond A.…”
Section: Methodsmentioning
confidence: 99%
“… Landmarks (black), curve (light blue), and surface (semi)landmarks (orange) digitized on a left fibula ( A ), proximal fibula, medial view; ( B ), proximal fibula, lateral view; ( C ), proximal fibula, posteromedial view; ( D ), distal fibula, medial view; ( E ), distal fibula, lateral view; ( F ), distal fibula, posterior view. See Table 2 for a detailed description of the anatomical landmarks [ 37 ] (license: CC BY 4.0). …”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations